DIGITAL PHOTOGRAPHY AND THE FUTURE OF PHOTOGRAPHY CULTURE - Hishamuddin, Siri; Mohd. Zahuri, Khairani; Hakimi, Halim (UNIMAS Publisher, 2022)
This paper aims to review the current situation on how Photography has completely changed the way we see and engage with the world. The shift from analogue to digital Photography significantly impacted how an analogue photographer perceives the photo process. In the age of these diverse prosumers, the distinction between artists, media professionals, and amateurs may still denote varying degrees of craftsmanship. However, it no longer indicates the inherent technical or aesthetic quality of the results or the likely size of an audience. The impacts give the impression that the aesthetics and attention of Photography provided revolution change in the society of arts and Photography. From this perspective, Photography has first been chemical, then optical and now computational. The changing identities of Photography herein are not simply ontological transformations but also errant modes of perceiving the medium.